Using the 5E Learning Cycle with Metacognitive Technique to Enhance Studentsâ Mathematical Critical Thinking Skills - Runisah, Runisah; Herman, Tatang; Dahlan, Jarnawi Afgani (Universitas Ahmad Dahlan, 2017)
This study aims to describe enhancement and achievement of mathematical critical thinking skills of students who received the 5E Learning Cycle with Metacognitive technique, the 5E Learning Cycle, and conventional learning. This study use experimental method with pretest-posttest control group design. Population are junior high school students in Indramayu city, Indonesia. Sample are three classes of eighth grade students from high level school and three classes from medium level school. The study reveal that in terms of overall, mathematical critical thinking skills enhancement and achievement of students who received the 5E Learning Cycle with Metacognitive technique is better than students who received the 5E Learning Cycle and conventional learning. Mathematical critical thinking skills of students who received the 5E Learning Cycle is better than students who received conventional learning. There is no interaction effect between learning model and school level toward enhancement and achievement of studentsâ mathematical critical thinking skills.